2019
DOI: 10.1162/jocn_a_01427
|View full text |Cite
|
Sign up to set email alerts
|

Not-so-working Memory: Drift in Functional Magnetic Resonance Imaging Pattern Representations during Maintenance Predicts Errors in a Visual Working Memory Task

Abstract: Working memory (WM) is critical to many aspects of cognition, but it frequently fails. Much WM research has focused on capacity limits, but even for single, simple features, the fidelity of individual representations is limited. Why is this? One possibility is that, because of neural noise and interference, neural representations do not remain stable across a WM delay, nor do they simply decay, but instead, they may “drift” over time to a new, less accurate state. We tested this hypothesis in a functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…At the neural level, evidence for drift has been found in the neural population code in monkey prefrontal cortex (PFC) during a spatial WM task [15], in which trial-wise shifts in the neural tuning profile predicted whether recall error was clockwise (CW) or counterclockwise (CCW) relative to the correct location. Recently, a human functional MRI (fMRI) study has found that delay activity reflected the probe stimulus more when participants erroneously concluded that it matched the memory item [16], which is consistent with the drift account.…”
Section: Introductionmentioning
confidence: 65%
“…At the neural level, evidence for drift has been found in the neural population code in monkey prefrontal cortex (PFC) during a spatial WM task [15], in which trial-wise shifts in the neural tuning profile predicted whether recall error was clockwise (CW) or counterclockwise (CCW) relative to the correct location. Recently, a human functional MRI (fMRI) study has found that delay activity reflected the probe stimulus more when participants erroneously concluded that it matched the memory item [16], which is consistent with the drift account.…”
Section: Introductionmentioning
confidence: 65%
“…(For example, averaging ERPs with different latencies can produce a grand average that appears lower in both amplitude and frequency than any individual trial's ERP actually is). In our own prior work, we have most certainly found that MVPA enabled us to address questions that could not be answered with previous univariate approaches; for example, that scene-selective visual brain areas represented not only category but exemplarlevel information during mental imagery (Johnson and Johnson, 2014), that ERPs related to mental attention that did not exhibit reliable differences between stimulus categories at a grandaverage level still contained category information with MVPA (Johnson et al, 2015), and that gradual drift in fine-grained information patterns in visual cortex during working memory could be used to predict memory errors (Lim et al, 2019).…”
Section: The Case Against Deep Learningmentioning
confidence: 99%
“…Numerous MVPA variations exist, including those based on correlation (either Pearson or rank-based; Haxby et al, 2001), support vector machines (SVMs; De Martino et al, 2008;Dosenbach et al, 2010), logistic regression (Akama et al, 2012), sparse multinomial logistic regression (SMLR; Krishnapuram et al, 2005;Kohler et al, 2013), naïve Bayes classifiers (Kassam et al, 2013), and more. Many of these techniques concern classification of brain patterns into discrete cognitive states, whereas others examine different aspects of the data (e.g., overall similarity between brain patterns; Xue et al, 2010;Lim et al, 2019) without explicit categorization, but all of them represent increases in mathematical and conceptual sophistication over univariate techniques. Importantly, when compared to earlier univariate techniques, MVPA has enabled us to examine in a much more nuanced fashion how brain activity patterns encode mental states.…”
mentioning
confidence: 99%
“…Numerous MVPA variations exist, including those based on correlation (either Pearson or rank-based; Haxby et al, 2001), support vector machines (SVMs; De Martino et al, 2008;Dosenbach et al, 2010), logistic regression (Akama et al, 2012), sparse multinomial logistic regression (SMLR; Kohler et al, 2013;Krishnapuram et al, 2005), naïve Bayes classifiers (Kassam et al, 2013), and more. Many of these techniques concern classification of brain patterns into discrete cognitive states, whereas others examine different aspects of the data (e.g., overall similarity between brain patterns; Xue et al, 2010;Lim et al, 2019) without explicit categorization, but all of them represent increases in mathematical and conceptual sophistication over univariate techniques. Importantly, when compared to earlier univariate techniques, MVPA has enabled us to examine in a much more nuanced fashion how brain activity patterns encode mental states.…”
Section: Introductionmentioning
confidence: 99%